Analysis of gilded teeth from the 11th–13th c. burial in the Zmeyskiy cemetery (Republic of North Ossetia — Alania) - S.Yu. Frizen; E.S. Vashchenkova; A.Yu. Loboda; N.N. Presnyakova; V.M. Pozhidaev; V.M. Retivov; E.Yu. Tereschenko; M.A. Bakushev; S.V. Vasiliev; E.B. Yatsishina (Вестник археологии, антропологии и этнографии, 2020)
Presented are the results of analysis of paleoanthropological materials — two teeth with gilded surface — found in catacomb 62 (Excavation III) of the Zmeyskiy burial ground (Stn Zmeyskaya, Kirovsky District, North Ossetia — Alania). The burial is dated to the 11th–12th c. This material is unique both for the area and the cultural tradition, and for the specified period. The scanning electron microscopy with energy-dispersive X-ray microanalysis, gas chromatography mass-spectrometry and inductively coupled plasma mass spectrometry were used. It has been determined that gilding was performed using organic binders — a mixture of animal fat, linseed and hemp oils. Based on the coating weakness, as well as traces of gilding detected on the dentin below the enamel layer, it has been concluded that the gilding process was postmortem. The analysis of composition of gold (Au 86.2 wt%, Ag 13.2 wt%), micro- and trace impurities, and its comparison with published data made it possible to attribute this gold to epithermal Au-Ag ores.